2014
DOI: 10.3727/096504014x14077751730351
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4 Enhances Osteosarcoma Cell Proliferation and Invasion by Akt Signaling Pathway

Abstract: TRAF4, or tumor necrosis factor receptor-associated factor 4, is overexpressed in several cancers, suggesting a specific role in cancer progression. However, its functions in osteosarcoma are unclear. This study aimed to explore the expression of TRAF4 in osteosarcoma tissues and cells, the correlation of TRAF4 to clinical pathology of osteosarcoma, as well as the role and mechanism of TRAF4 in osteosarcoma metastasis. The protein expression levels of TRAF4 in osteosarcoma tissues and three osteosarcoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The results of the present study demonstrated that inhibition of the expression of TRAF4 using siRNA in RBE and HCCC9810 cells impaired their motility and invasiveness of capabilities. Mechanistically, it was found that the downregulation of TRAF4 in ICC cells significantly inhibited the activation of AKT signaling in vitro, similarly consistent with previous studies (21,24). Furthermore, the AKT inhibitor perifosine eradicated the effect of TRAF4 on the ICC cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the present study demonstrated that inhibition of the expression of TRAF4 using siRNA in RBE and HCCC9810 cells impaired their motility and invasiveness of capabilities. Mechanistically, it was found that the downregulation of TRAF4 in ICC cells significantly inhibited the activation of AKT signaling in vitro, similarly consistent with previous studies (21,24). Furthermore, the AKT inhibitor perifosine eradicated the effect of TRAF4 on the ICC cells.…”
Section: Discussionsupporting
confidence: 89%
“…It was previously reported that the upregulation of TRAF4 increased the mobility and invasiveness of HCC cells in vivo and in vitro, and increased the level of the transcription factor slug, which acts as a key inducer of the EMT process, via activation of the PI3K/AKT signaling pathway (21). Yao et al (24) showed that TRAF4 fosters AKT membrane recruitment and, crucially, binds directly to AKT to promote the proliferation and invasion of breast cancer cells. In addition, TRAF4 directly interacts with TGF-β protein, and enhances TGF-β-induced small mothers against decapentaplegic (SMAD) and non-SMAD signaling to drive breast cancer metastasis (22).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The human osteosarcoma U2OS cell line is a well-established and widely used model system of osteosarcoma cells (Lucero et al, 2013;Spina et al, 2013a;Yao et al, 2014).…”
Section: Adomet Inhibits Proliferation Of Human Osteosarcoma U2os Cellsmentioning
confidence: 99%
“…Upregulation of the former has been significantly implicated in OS pathogenesis, resulting in increased proliferation, increased invasion, and decreased apoptosis of tumor cells [90] . Researchers have shown that various molecules cause this activation, including the long noncoding RNA metastasis-associated Current status of osteosarcoma biology and therapy lung adenocarcinoma transcript 1 (MALAT1), tumor necrosis factor receptor-associated factor 4 (TRAF 4), and autophagy related protein 6 (Beclin-1) [91][92][93] . Furthermore, suppressing such activation may not only be involved in decreasing the aggressiveness of tumors, but may also be involved in overcoming chemoresistance, further demonstrating the importance of PI3K/ AKT signaling as a therapeutic target [91,[94][95][96][97] .…”
Section: Signaling Pathway Dysregulationmentioning
confidence: 99%